Implementasi Maqashid Syariah dalam Regulasi Fintech Syariah: Analisis Yuridis-Normatif Terhadap Perlindungan Konsumen di Indonesia - Maryani; Ahmadi; Munawar Zulfikar; Sisliandri; Muhammad Ridho Saputro (Jurnal Hukum Caraka Justitia, 2026)
The rapid growth of Islamic financial technology (Syariah fintech) in Indonesia presents unique challenges in striking a balance between Sharia compliance and consumer protection mechanisms. Although regulatory frameworks from the OJK and DSN-MUI are in place, significant gaps remain in the implementation of maqashid Syariah principles within fintech operations. This study examines the extent to which Indonesia’s Syariah fintech regulations incorporate maqashid sharia principles for consumer protection, identifies regulatory gaps, and proposes a comprehensive framework for addressing these gaps. Using a juridical-normative approach, the research analyzes primary legal sources, including Law No. 21/2008, OJK Regulation No. 77/2016, and DSN-MUI Fatwas, as well as secondary sources from Scopus- and SINTA-indexed journals. The findings reveal three critical gaps: inadequate operationalization of the maslahah principle in algorithmic decision-making, limited protection against predatory lending practices, and insufficient Syariah-specific complaint mechanisms. Effective consumer protection in Syariah fintech requires regulatory reforms that embed maqashid sharia principles into licensing requirements, operational standards, and dispute resolution mechanisms through a three-tiered regulatory framework.